1994
DOI: 10.1002/jts.2490070403
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of sexual abuse: Content analysis of interviews with male survivors

Abstract: Autobiographical interviews with 26 adult male survivors of childhood sexual abuse were audiotaped, transcribed verbatim and content analyzed to identify common psychological themes. Approximately equal numbers of men were abused by male and female perpetrators, almost half came from disrupted or violent homes and a majority had a history of substance abuse. Fifteen psychological themes were identified: Anger, Betrayal, Fear, Homosexuality Issues, Helplessness, Isolation and Alienation, Legitimacy, Loss, Mascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(72 citation statements)
references
References 18 publications
4
63
1
4
Order By: Relevance
“…Greater social visibility of SV against boys can help victims who have difficulty reporting the abuse (Alaggia, 2005;Sorsoli et al, 2008), often because of doubts about their sexual orientation (Lisak, 1994;Romano & De Luca, 2001), as the SV is usually perpetrated by a male abuser (Hohendorff et al, 2012, Kristensen, 1996Pinto Junior, 2005;Pires Filho, 2009;Prado, 2006) that can make the boys believe they are homosexual. Prevailing standards of masculinity based on independence and stoicism (Sanderson, 2005) also contribute to the social invisibility of SV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater social visibility of SV against boys can help victims who have difficulty reporting the abuse (Alaggia, 2005;Sorsoli et al, 2008), often because of doubts about their sexual orientation (Lisak, 1994;Romano & De Luca, 2001), as the SV is usually perpetrated by a male abuser (Hohendorff et al, 2012, Kristensen, 1996Pinto Junior, 2005;Pires Filho, 2009;Prado, 2006) that can make the boys believe they are homosexual. Prevailing standards of masculinity based on independence and stoicism (Sanderson, 2005) also contribute to the social invisibility of SV.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario can be explained by factors such as finding that male victims do not disclose or have greater difficulty revealing SV and that professionals fail to suspect or investigate the possible occurrence of SV in boys and men (Holmes & Offen, 1997). Although fewer in number, studies with male victims, mainly adults with a history of SV in childhood, indicate that the difficulty for boys to reveal SV (Alaggia, 2005;Sorsoli, Kia-Keating, & Grossman, 2008) leads to consequences such as somatization, obsessive-compulsive symptoms, depression, anxiety and hostility, interpersonal difficulties, phobic anxiety, paranoid ideation and psychosis (Collings, 1995), stress (Steever, Follete, & Naugle, 2001), emotional problems (e.g., anger, helplessness and shame), cognitive distortions (e.g., selfblame and inability to consider their experience as violence), interpersonal difficulties (e.g., sense of betrayal, isolation) and problems related to sexuality and sexual orientation, which were more frequent in victims sexually violated by men (Lisak, 1994). Reviews of the international literature have corroborated these results (Romano & De Luca, 2001) and reported the characteristics of the victims, abusers and the SV itself (Holmes & Slap, 1998).…”
mentioning
confidence: 99%
“…Traditional masculinity opposes anything associated remotely with femininity, equating it with passivity and helplessness (Hong, 2000;Lisak, 1994). Stoicism, homophobia, and dominance serve to prove one's maleness (Hong, 2000).…”
Section: Masculinity and Childhood Sexual Abusementioning
confidence: 99%
“…Having received the brunt of aggression and power in the role of victim, one trajectory taken by a minority but significant number of abused men is to react by becoming hypermasculine; in other words, hyperaggressive, overcontrolled, unemotional, action oriented, and abusive to others (Gartner, 1999;Lisak, 1995). In one study, 31% of a sample of 26 sexually abused men carried the legacy of abuse and reported acting as perpetrators of violence at some point in their life (Lisak, 1994).…”
Section: Masculinity and Childhood Sexual Abusementioning
confidence: 99%
See 1 more Smart Citation